Evolution of Earnings and Rates of Returns to Education in Mexico - Lopez-Acevedo, Gladys (World Bank, Washington, DC, 2014)
Reviewing the factors, and mechanisms that have been driving inequality in earnings in Mexico, the author finds that inequality in education, accounts for the largest share by far of the variation in earnings. In fact, the contribution of educational inequality to earnings inequality in Mexico, ranks second in size in Latin America, after that in Brazil, and its significance has been increasing. Moreover, the income effect is always prevalent, and the distribution of education is highly significant, even after controlling for changes in other relevant variables, such as age, region, economic sector, and labor market status. But the increase in earnings inequality in Mexico, does not appear to be the result of a worsening in the distribution of education - although the income profile, which is related to returns to schooling, has become much steeper. This means that the shift in demand toward high-skilled labor, has not been matched by an increase in supply. The probable reason: the increased economic openness in Mexico has facilitated skill-biased technological change.